Strategies for Forming the Image of Islam/Muslims in the Media Discourse - Tatyana S. Pronina; Varvara A. Slivkina (Changing Societies & Personalities)
The article explores the process of constructing the image of Islam and Muslims in media discourse, focusing on publications from Saint Petersburg and the Leningrad Oblast (Russia) over the past two decades. The research employs the analytical reading of text data, following the grounded theory method. The focus is made on themes such as the European migration crisis and the rise of Islamic migration to Europe and Russia, debates over wearing the hijab in Russian schools, and coverage of Muslim religious holidays and ethnic festivals like Sabantuy. The study also addresses city incidents, events linked to extremist and terrorist activities, and the portrayal of Muslims in the context of Russia’s demographic landscape. Additionally, it highlights how the Muslim community is represented within the framework of a multi-confessional and multi-ethnic urban environment. The analysis of the empirical material leads the authors to identify two primary strategies employed by local media in constructing the image of Islam and Muslims. These strategies reflect both challenges and opportunities for fostering understanding and cooperation within diverse societies. The authors conclude that promoting inclusion and ensuring a peaceful future require long-term efforts, including educational initiatives and consistent work to combat stereotypes and prejudice in media narratives.